Equilibrium - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2023)
Fire is the only source of heat and light energy. It is often wondered what is the principle governing the movement of energy. This paper describes that. The principle governing movement of energy (or heat energy) is thermal equilibrium [1]. This is the condition governing movement of energy. Examples of thermal equilibrium could be found in atmosphere and man-made objects [1].